2013
DOI: 10.1007/s13224-012-0335-5
|View full text |Cite
|
Sign up to set email alerts
|

Mid-second Trimester Measurement of Nasal Bone Length in the Indian Population

Abstract: We have established the nasal bone length in South Indian fetuses at 16-26 weeks of gestation and there is progressive increase in the fifth percentile of nasal bone length with advancing gestational age. Hence, gestational age should be considered while defining hypoplasia of the nasal bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
2
16
2
4
Order By: Relevance
“…Following the criteria of measurement, a normal Vietnamese reference for fetal NBL at 19–26 weeks’ gestation was identified. Fetal NBL increases significantly with gestational age and BPD, in accordance with previous monosonographer reports . The present 50th percentile of fetal NBL was longer than that noted by Narayani and Radhakrishnan in India, but it was closely matched by Kanagawa et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Following the criteria of measurement, a normal Vietnamese reference for fetal NBL at 19–26 weeks’ gestation was identified. Fetal NBL increases significantly with gestational age and BPD, in accordance with previous monosonographer reports . The present 50th percentile of fetal NBL was longer than that noted by Narayani and Radhakrishnan in India, but it was closely matched by Kanagawa et al .…”
Section: Discussionsupporting
confidence: 92%
“…At the second trimester of gestation, there is a higher proportion of nasal bone in the total volume of osteo‐cartilaginous tissue in the fetus with normal karyotype than in Down syndrome fetuses (the ratio is 35–50% of bone tissue in fetal euploidy versus 10–20% in trisomy 21) . Several studies have proposed an association between delayed ossification of fetal nasal bone and Down syndrome, but delayed maturation has also been noted in fetuses without abnormalities, depending on maternal ethnicity …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mid-second trimester foetal nasal bone measurements in healthy Chinese population was shorter than in White and Black population. Bundeppa et al (2) have also observed that race and ethnicity have an impact on foetal bone length.…”
Section: Discussionmentioning
confidence: 94%
“…4 gives comparative values of nasal bone length in foetuses of North Indian and South Indian. (2) Caucasian. (1) , Brazilian.…”
Section: Discussionmentioning
confidence: 99%